A Medical Resident with a History of Alcohol Abuse and Suicidal Ideation: A Challenge for Both Psychiatry and Occupational Medicine in the Context of the First Wave of the COVID-19 Pandemic. (17th October 2022) - Corsi, Martina; Veltri, Antonello; Perretta, Salvio; Marino, Riccardo; Necciari, Gabriele; Caldi, Fabrizio; Foddis, Rudy; Cristaudo, Alfonso; Buselli, Rodolfo; Guglielmi, Giovanni
Abstract : This case study draws attention to the hazards of physicians with a history of alcohol addiction and a particular psychopathology framework in the context of occupational health surveillance, particularly during the challenging working conditions brought about by the COVID-19 pandemic. The case involves a hospital resident in her thirties, with a previous history of addiction and attempts at suicide, who was assigned to a COVID-19 unit of an Italian hospital. In this case study, we discuss the preventive intervention put in place in order to protect physicians' health and work. What emerges is the key role that rapid substantive communications between specialists play in formulating an effective strategy for dealing with these conditions. We believe this case is noteworthy for the lessons that can be learned for tailoring prevention and treatment pathways for health care workers with addiction.